Estrutura filogenética de metacomunidades ao longo de gradientes ambientais - Provete, Diogo Borges (2015)
Phylogenetic information has increasingly been included in studies of local communities and also at broad spatial scales. Despite recent criticisms in the last four years, phylogenetic relationships may still provide insights into the organization and assembly of ecological communities. The objectives of this study were 1) to review the history of the use of phylogenetic information, as well as criticisms and perspectives of its use in community ecology; 2) understand how the size and shape of phylogenetic trees and the phylogenetic structure of metacomunidaes affect the amount of variation accounted for by a eigenvector-based method used to describe the phylogenetic composition of metacomunidaes (PCPS); 3) to test the effect of diversity of evolutionary history (MNTD and MPD) and species richness as predictors of three variables of freshwater ecosystem functioning (productivity, respiration, and decomposition); and finally 4) to test how environmental gradients, especially pond canopy cover, influence the phylogenetic structure of an anuran metacommunity from southeastern Brazil. I found that the structure of metacommunities had greater impact on eigenvalues of PCPS than tree shape metrics, such as symmetry and stemminess. In addition, decomposition and respiration were best predicted by MNTD as a linear function, while productivity was affected by the quadratic term of MNTD. Finally, pond canopy cover and floating vegetation strongly affected the phylogenetic structure of the anruan metacommunity, influencing lineage sorting. These findings 1) can help users interpret the results of PCPS; 2) provide better understand of the effect of species loss in multitrophic, freshwater ecosystems; and 3) improve our knowledge about the effect of canopy cover on the lineage composition in anuran metacomunities.